“Hello, My Name Is Melinda” – Students' Views on a Digital Assistant for Navigation in Digital Learning Environments; A Qualitative Interview Study - Herrmann-Werner, Anne; Loda, Teresa; Junne, Florian; Zipfel, Stephan; Madany Mamlouk, Amir (Frontiers in Education, 2021)
Background: The goal of the current investigation was to find out about students attitudes and needs towards the development of a new personal digital assistant (PDA) to help them navigate through an increasingly digital learning environment (DLE). As students have repeatedly been shown to be an especially stress-prone user-group, a PDA serving as a digital secretary might additionally significantly reduce study-related stress. Methods: N = 12 STEM (science, technology, engineering and math) students in various years of study at the University of Luebeck, Germany, participated in the study. A qualitative research design of semi-structured interviews was used with the interviews evaluated according to Mayring’s qualitative content analysis (Mayring, 2015) using MAXQDA Version 2018. Results: Students being educated in a DLE in many cases report positive as well as negative impacts on communication through progressing digitalisation. In line with previous findings, students indicated several study-related and personal stressors during their academic life, but they also reported a variety of preventive factors such as motivation and interest in their studies as well as social support. When asked specifically about desired functions of a future PDA, students wished for a kind of digital secretary with functions such as recording, calendarisation and automated exam registration. Conclusions: Valuable insights were obtained regarding all areas of interest – DLE, stressors and preventive factors of students being educated within DLE, and ideas regarding the development of a new, student-user-friendly PDA. Previous results from stress research in student samples combined with the insights from the present study support the thought that a PDA combining administrative and counselling functions might be a new idea for students and could potentially complement a simple administrative PDA, additionally helping to provide students with therapeutic or counselling needs.